Isotherm, kinetic and thermodynamic investigations of boron phosphide to remove methylene blue from aqueous solution - Yildirim, Furkan Murat; Isik, Birol; Ugraskan, Volkan (JOURNAL OF CENTRAL SOUTH UNIV, 2024)
In this work, the boron phosphide (BP) was synthesized and used for the adsorptive removal of methylene blue (MB) dye from aqueous solutions. To determine the optimum adsorption conditions, studies were performed by varying parameters of temperature (298-328 K), pH (2-12), contact time (0-120 min), adsorbent dose (0.01-0.20 g/50 mL), and dye concentration (10-50 mg/L). Different isotherm and kinetic models were applied to the adsorption data. The linear correlations coefficient showed that the Langmuir isotherm best fits (R-2=0.9996). The maximum adsorption capacity of BP was obtained as 555.56 mg/g at 55 degrees C and the removal rate reached up to 84.11%. Additionally, the pseudo-second-order kinetic model described the adsorption process best (R-2=0.9998). The thermodynamic studies represented that the adsorption occurred spontaneously (Delta G(A)(Theta) = - 24.90 kJ/mol) and endothermically (Delta H-A(Theta)=16.67 kJ/mol). The results showed that BP is an efficient adsorbent for removing cationic dyes from aqueous solutions.
Keywords: adsorption; boron phosphide; methylene blue; DYE ADSORPTION; NANOPARTICLES; Metallurgy & Metallurgical Engineering